Theatre & human rights - Rae, Paul (Theatre, 2009)
With its impassioned plays, inspired activism and outspoken artists, the theatre has long provided a venue for promoting and practising human rights. Drawing on a range of international examples, this title examines the challenges presented by the contested relationship between theatre and human rights.